Globalisation : studies in anthropology - Eriksen, Thomas Hylland (Pluto Press, 2003)
Globalisation has had a massive impact on the teaching and practice of anthropology. This important new book, edited by leading anthropologist Thomas Hylland Eriksen, addresses the methodological problems that these changes have wrought, and in doing so fills a major gap in the contemporary study and teaching of anthropology. The essays in this book show how the focus has shifted from traditional studies of specific sites, towards the movements and shifts assoicated with increasing migration and population flows -- the result of living in an increasingly globalised world. Written by a range of distinguished anthropologists, it offers innovative new approaches to the discipline in the light of these changes, making it indispensable as a teaching text, at higher levels, and as mandatory reading for practitioners and researchers in a wide range of merging disciplines. Topics explored include the methodology of studying on the internet; global and spatial identities in the Caribbean; shifting boundaries in coastal communities; the anthropology of political life; issues of law and the flow of human substances; and the diffusion of moral values created by globalisation.
Keywords: Anthropology.; Globalization.; Law and anthropology.; Ethnology -- Methodology.; Transnationalism.; Culture diffusion.; Emigration and immigration.; Anthropology; Emigration and Immigration; Ethnologie -- Méthodologie.; Mondialisation.; Transnationalisme.; Diffusion culturelle.; Émigration et immigration.; Anthropologie.; Droit et anthropologie.; anthropology.; globalism.; cultural diffusion.; immigration.; Migration period (Medieval culture or period); emigration.; migrations (events); SOCIAL SCIENCE -- Regional Studies.; SOCIAL SCIENCE -- Anthropology -- General.; SOCIAL SCIENCE -- Anthropology -- Cultural.; Transnationalism; Ethnology -- Methodology; Emigration and immigration; Culture diffusion; Globalization; Law and anthropology; Anthropologie; Globalisierung; Culturele antropologie.; Internationalisatie.; Methodologie.